World Environmental and Water Resources Congress 2014 2014
DOI: 10.1061/9780784413548.105
|View full text |Cite
|
Sign up to set email alerts
|

Many-Objective Direct Policy Search in the Dez and Karoun Multireservoir System, Iran

Abstract: In this study we propose a novel approach to design Pareto-optimal operating policies via many-objective direct policy search in the Dez and Karoun multireservoir system (Iran), where the dimension of the system, the dry climate, and the presence of competing demands pose a number of challenges to water planners and managers. The three power plants connected to the main reservoirs in the modeled system (i.e., Dez, Karoun, and Masjed Soleyman) account for 20% of the national hydropower generation capacity. Irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Controlling a network of five storages using such a low number of decision variables significantly reduces computational complexity compared to prior DPS approaches. For instance, Biglarbeigi et al (2014) used 117 parameters to optimize the release policy of a network of three reservoirs. Giuliani et al (2018) used 176, and 134 parameters for a system consisting of four reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling a network of five storages using such a low number of decision variables significantly reduces computational complexity compared to prior DPS approaches. For instance, Biglarbeigi et al (2014) used 117 parameters to optimize the release policy of a network of three reservoirs. Giuliani et al (2018) used 176, and 134 parameters for a system consisting of four reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…The direct policy search expresses a release policy using a given family of parameterized functions (Deisenroth et al 2013). It was also extended to multiobjective problems (Biglarbeigi et al 2014) and MOEAs were used to solve it. For instance, Giuliani et al (2016) found radial basis functions (RBF) to be particularly useful for this task.…”
Section: Introductionmentioning
confidence: 99%
“…Each optimization was run for 100,000 function evaluations. The analysis of runtime progress of the optimization(Biglarbeigi 2014) ensures the attainment of high fidelity approximations of the Pareto approximate set with this number of function evaluations. To improve solution diversity and avoid dependence on randomness, we run 20 independent optimization trials.…”
mentioning
confidence: 99%